The study of microbial flora on doctors white coats in tertiary care hospital in outskirts of Hyderabad, Telangana, India - Noor, Fadila; Jayanthi, R. Saraswati (International Journal of Research in Medical Sciences, 2017)
Background: White coats are known to harbour microorganisms; this study aims to determine the microorganisms present on the white coat and investigate the factors associated with contamination, reasons for wearing, usage and attitudes of doctors towards the white coat. Methods: A cross sectional type of quantitative and qualitative study to determine the contamination of white coats. Participants completed a questionnaire and samples were taken from the cuffs and pockets of white coat. Results: 94% of the white coats screened were harbouring organisms. Diphtheroids are the most common bacterial isolate and Aspergillus is the only fungal isolate. The medical speciality, frequent washing and the use of disinfectants is associated with decreased contamination. Conclusions: As white coats harbour microorganisms, this may result in transmission of these microorganisms to the patients and that may result in nosocomial infections, especially in the immuno-compromised. Therefore, measures need to be taken to decrease this risk of transmission by hand washing and frequent washing of white coats with disinfectants.